Implementasi Model Pembelajaran PJBL Untuk Meningkatkan Hasil Belajar Seni Tari SMA Negeri 8 Denpasar - Gusti Ayu Made Puspawati; Sindy Noviantari Subiartha; Mirah Rahmawati (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
The arrangement of Classroom Activity Investigate at SMA Negeri 8 Denpasar was propelled by the comes about of introductory perceptions which appeared issues related to moo understudy learning results in move subjects. Subsequently, this investigate points to move forward move learning results utilizing the PJBL Learning Show with the Peer Mentor Strategy. This sort of investigate comprises of two cycles, each cycle has four stages, specifically arranging, executing activities, watching and reflecting. The subjects of this investigate were 30 understudies of lesson XII IPS 3. This inquire about was carried out from April to May 2024. The information collection procedures utilized were perceptions with respect to the execution of activities and the comes about accomplished, interviews, and worksheet appraisals. The information examination procedure is subjective clear investigation utilizing the PJBL learning demonstrate with the peer mentoring strategy to test the comes about of understudy introduction appraisals by comparing the normal score of completeness of learning results. The investigate comes about appeared that the normal move learning results had expanded from cycle I to cycle II. This may be seen from the normal increment gotten from the comes about of the introduction evaluation. The normal course score in cycle I was with the most noteworthy score of 78 and the least score of 63. In the mean time in cycle II the normal lesson score was 87, with the most elevated score being 90 and the most reduced score being 82.